Pengaruh Substitusi Mocaf dan Jewawut pada Makanan Tradisional Jepa - Mayangsari, Riska; Kasma, Andi Sri Rahayu (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to assess the effect of mocaf and millet substitution on traditional Jepa food. This study was conducted using a one-factor Randomized Block Design method. The development of modified jepa was carried out with three treatments and three replications. The first treatment was traditional jepa with a composition of cassava (25g) and coconut (20g); the second treatment was mocaf-modified jepa with a composition of mocaf flour (20g), and coconut (30g); and the third treatment was wet millet flour (20g) and coconut (30g). All treatments were tested organoleptically by trained panelists, followed by proximate analysis on the three samples. The results of this study indicate that the substitution of mocaf and millet in traditional Jepa food can increase the liking for jepa and improve its nutritional value.